ACUTE APPENDICITIS: GAINING TIME IN MASS CASUALTY SCENARIO: Acute Appendicitis in Casualty Scenario - Hanif, Major Muhammad Shoaib; Tahir, Tufail Hussasin; Sheikh, Irfan Ali; Ranjha, Muhammad Zaman (Pakistan Armed Forces Medical Journal, 2010)
Objective: To find out group of drugs best to gain time before appendicectomy in patients of acute appendicitis in mass causalities scenario.Study Design: Quasi-Experimental.Place and Duration of study: A post earthquake, resource constrained hospital taking care of dependant population of three districts at CMH RawlaKot from 15 Jan 2007 to 15 Jan 2008.Patients and Methods: Ten patients were selected in each group by convenience sampling. Patients were divided into five groups Group I No Antibiotics, Group II Ampicillin / Gentamicin / Metronidazole, Group III Ceftriaxone / Metronidazole, Group IV Ampicillin / Sulbactum, Group V Cefoperazone / Sulbactum. Group I was taken as control where the appendectomy delay was according to the natural history of the disease. Group II, III, IV & V who had to be triaged and placed on antibiotics regimen before operation. Extreme care was taken so that this approach was only adopted in patients where the delay in appendectomy was inevitable. All patients were operated 24 to 72 hours after onset of symptoms. The grade of operative difficulty was assessed objectively and average difficulty scores were compared between the groupsResults: In the one year period 431 appendectomies were performed out of which 50 patients were included in the study. These 50 comprised of 10 patients in each group. Overall male to female ratio was 27:23. Overall average age was 25.14 + 7.54. In Group I an average delay before presentation 57.6 + 12.39 hrs. In Group II to V the overall delay from start of symptoms till operation was 55.63 + 8.37 hrs. The cumulative ease to operative was experienced in group V.Conclusion: In scenario of mass / multiple casualty, the antibiotic containing sulbactum will be best empirical therapy to gain time for patients of acute appendicitis. The one having Cefoperazone has got a definitive edge over the rest.